Molecular Modeling Studies on the Multistep Reactivation Process of Organophosphate-Inhibited Acetylcholinesterase and Butyrylcholinesterase - Jończyk, Jakub (Biomolecules, 2021)
Poisoning with organophosphorus compounds used as pesticides or misused as chemical weapons remains a serious threat to human health and life. Their toxic effects result from irreversible blockade of the enzymes acetylcholinesterase and butyrylcholinesterase, which causes overstimulation of the cholinergic system and often leads to serious injury or death. Treatment of organophosphorus poisoning involves, among other strategies, the administration of oxime compounds. Oximes reactivate cholinesterases by breaking the covalent bond between the serine residue from the enzyme active site and the phosphorus atom of the organophosphorus compound. Although the general mechanism of reactivation has been known for years, the exact molecular aspects determining the efficiency and selectivity of individual oximes are still not clear. This hinders the development of new active compounds. In our research, using relatively simple and widely available molecular docking methods, we investigated the reactivation of acetyl- and butyrylcholinesterase blocked by sarin and tabun. For the selected oximes, their binding modes at each step of the reactivation process were identified. Amino acids essential for effective reactivation and those responsible for the selectivity of individual oximes against inhibited acetyl- and butyrylcholinesterase were identified. This research broadens the knowledge about cholinesterase reactivation and demonstrates the usefulness of molecular docking in the study of this process. The presented observations and methods can be used in the future to support the search for new effective reactivators.